The changing role of subject librarians in academic libraries - Pinfield, Stephen (2001)
Discusses the roles that subject librarians (or 'subject specialists') play in contemporary UK academic libraries. Argues that subject librarians, who still form a significant grouping of senior staff in most UK academic libraries, continue to have a significant role to play in the delivery of library services and that applies to both traditional and electronic library services. Discusses the traditional role of subject librarians and analyzes the way in which this role is changing. Those areas where the changing responsibilities are extensions of traditional roles into new areas are pinpointed, together with examples of where subject librarians are performing new roles and adopting new ways of working. Areas where the changing role of subject librarians can be specifically identified include: greater emphasis on liaison with users; advocacy of the collections; adopting new roles; dealing with user enquiries in new ways; working with technical staff; selecting electronic library materials; carrying out more information skills training; having a greater involvement in the implementation of educational technology; team working and project working. Presents practical examples based on experiences at Nottingham university and other UK research libraries. The redesign and relaunch of Nottingham University Library Web site is described to illustrate many of these points.